Analyzing the Quality of Game-based Assessment Design in Basic Arithmetic Operations - Azzmi. H., M. Naufal; Yuhana, Umi Laili; Sulistyani, Nawang; Husniah, Lailatul (Universitas Muhammadiyah Malang, 2023)
The use of Serious Games in education has experienced rapid development. However, not all studies have been able to show evidence that game-based methods are superior to other methods. It is important to analyze the quality of game designs used in learning and assessment used to assess students. This study focuses on how to design a serious game called B-block used in the assessment. The researcher validates the quality of the serious game first before conducting a pilot study regarding the feasibility of the Serious Game given for assessment. The game focuses on basic arithmetic, including addition, subtraction, division, and multiplication, and involves positive and negative numbers. The study was conducted in one of the schools in Indonesia and given to 35 students with an age range of 11-12 years with different student backgrounds in their experience with game-based exams. Based on these results, 85.7% of respondents agreed that this game could be used as a substitute for paper-based exams, with the analysis of game design quality having an average value of 78% pedagogic specifications and 73% playful and 80% technical specifications. Thus, the average value of this game quality analysis is considered superior and meets almost all the specifications needed for assessment. We also argue that serious game is closely related to how game design meets specifications for use as educational tools.